Tindak Tutur Perbualan bersama Golongan Badwi dan Ansar: Analisa Strategi Komunikasi Rasulullah - Mohd Faizal Kasmani; Nurul Asiah Fasehah Muhamad; Noornajihan Ja‘afar; Norzulaili Mohd Ghazali; Rozita Abdullah (UKM Press, 2024)
Indexed by WOS/ Scopus